I3-∇ algebras (1983)
In this note we present an algebraic study of a fragment of the three-valued propositional calculus of Lukasiewicz, that is, we study from an algebraic standpoint the three-valued calculus where the characteristic matrix is given by the chain T = {0,1/2,1} and the connectives → (Lukasiewicz  implication) and ∇ (possibility operator are given by the tables: